MECHANICAL PROPERTIES OF NANOCRYSTALLINE PRODUCED BY ELECTRODEPOTION: AN REVIEW - Suryani, S (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Electrodeposition of nanocrystalline is a technologically viable production route to synthesize alloys and metal matrix composites both in bulk from and as coating. Particle concentration in plating bath strongly affects the particle content in the composites produced. The presence of particles in composites changes their characteristics, making them better or worse with respect to tensile strength, hardness or surface texture. With decreasing grain size, the hardness materials initially increase following the regular Hall-Petch relationship.Key Words: Electrodeposition,nanocrystalline, production route, alloys, tensile strength